ADAPTED MOTOR ACTIVITIES AS EXISTENCES INSTRUMENT OF BASIC ABILITIES IN CHILDREN WITH DOWN'S SYNDROME (Fiep Bulletin - online, 2014)
The precocious stimulation of motor experiences, in children with Down's syndrome, is fundamental to improve his development. Syndrome of Down or trisomy 21. This work refers to the practice of physical activities for disabled children. The Program of Motor Activities for Disabled Person - PROAMDE, from Federal University of Amazons report the practice of motive activities, with a group composed by twenty children with several kinds of deficiency, in the of age band from 2 to 6 years. In the period 8 month, they were developed contents with: Locomotion (crawl, roll, walk in four supports, transpose obstacles and etc. Manipulation: launch, throw, grasp, tweezers and another. In the socialization, they were developed activities in little and great groups. Two children with Down's syndrome demonstrated a great evolution during this period 8 month. One is female and the other is male, both it has 3 years old. The PROAMDE It has as objective develops student's potentialities, propitiating discoveries situations that did not yet have knowledge. Strategies are adapted, creating possibilities so that the student reaches the success in the exercises achievements. It is performed a motor assessment at the beginning and at the end of year, to verify student's level motor. The classes were performed the Tuesday and Thursday, with duration of 1 hour and a half. The data collection, it was done through observation and described in individual accompaniments after every class. Like result of this work the significant improvement in the next aspects was observed: socialization; larger interaction with the colleagues. In the aspect motor improved the balance and the locomotion. Emotional, at the beginning the participation in the activities only was with the mother, with the activities process there was the detachment. The practice of Physical Activity with parents' participation brought important contributions, for the children development process with Down's syndrome.
Keywords: Motive activities; basic abilities